Drug micro-carriers with a hyaluronic acid corona toward a diffusion-limited aggregation within the vitreous body. (15th September 2019) - Mayol, Laura; Silvestri, Teresa; Fusco, Sabato; Borzacchiello, Assunta; De Rosa, Giuseppe; Biondi, Marco
Highlights: Microparticles were decorated with two different molecular weights hyaluronic acid. Hyaluronic acid corona discourage the diffusion of microparticles in the vitreous. The molecular weight of the hyaluronic acid influence protein release kinetics. Hyaluronic acid molecular weight influence the diffusion of the microparticles. Hyaluronic acid molecular weight does not affect degradation time of microparticles. Abstract: Posterior eye segment diseases are treated through monthly intravitreal injections, that evoke serious side effects. A promising approach to reduce injection frequency consists in producing biodegradable microspheres (MPs) releasing the protein in the vitreous body for long times. Moreover, a rational design of these MPs requires a discouraged diffusion/sedimentation within the intravitreal space, which are detrimental for the vision and the control over drug release kinetics. In this work, poly(lactic-co-glycolic acid) (PLGA)-based MPs encapsulating bovine serum albumin (BSA) were coated with hyaluronic acid (HA) at two molecular weights and tested for their release, diffusion and degradation features in simulated vitreous body (SVB). Results indicate that HA corona prolongs MP degradation time and BSA release. Furthermore, HA coating increased the affinity between MPs and SVB, thereby repressing device transport compared to control PLGA MPs. Results hold promise for the possible application of HA-decorated MPs for intravitreal injection of protein drugs.